ΑCGRP Affects BMSCs' Migration and Osteogenesis via the Hippo-YAP Pathway. Issue 11 (November 2019) - Wang, Bin; Lin, Jie; Zhang, Qin; Zhang, Xinyuan; Yu, Hui; Gong, Ping; Xiang, Lin
Alpha-calcitonin gene-related peptide (αCGRP) plays a significant pathophysiological role in the regulation of bone metabolism. Our previous research indicated that αCGRP might have a potential application in enhancing osseointegration in vivo. To further uncover the intrinsic mechanism of its networks in bone regeneration, here we investigate the impact of αCGRP on osteogenic differentiation in bone marrow-derived mesenchymal stem cells (BMSCs) from both wild-type and αCGRP -/- mice. Considering the half-life of αCGRP in plasma is only 10 min, we applied αCGRP lentivirus and stably transfected it into BMSCs, followed by transfection identification and cell cycle assay. We further conducted a series of in vitro tests, and the results revealed that biological functions including migratory ability and osteogenicity exhibited positive correlation with BMSCs' αCGRP expression. Meanwhile, this phenomenon was associated with an enhanced expression of YAP (Yes-associated protein), the key downstream effector of the Hippo pathway. To sum up, our data together with previous in vivo observations is likely to elucidate the intrinsic mechanism of αCGRP in bone remodeling, and αCGRP would appear to be a novel treatment to promote bone wound healing.